Long Non-coding RNA HOTAIR Function as a Competing Endogenous RNA for miR-149-5p to Promote the Cell Growth, Migration, and Invasion in Non-small Cell Lung Cancer - Li, Hang; Cui, Zhigang; Lv, Xiaoting; Li, Juan; Gao, Min; Yang, Zitai; Bi, Yanhong; Zhang, Ziwei; Wang, Shengli; Li, Sixuan; Zhou, Baosen; Yin, Zhihua (Frontiers in Oncology, 2020)
Lung cancer is a leading cause of cancer death all around the world. Long non-coding RNAs (lncRNAs) have been confirmed to be involved in carcinogenesis of malignancies. However, the molecular mechanism of most lncRNAs in various kinds of cancers remains unclear. LncRNA HOTAIR and HNRNPA1 are reported to play an oncogenic role in non-small cell lung cancer, and the overexpression of HNRNPA1 is shown to promote the proliferation of lung adenocarcinoma cells. In our study, we find that the overexpression of HOTAIR could promote the proliferation and overexpression of miR-149-5p could inhibit the proliferation of lung cancer cells. Flow cytometric analysis determines that overexpression of miR-149-5p induces cell cycle arrest in the G0/G1 phases, whereas overexpression of HOTAIR decreases the proportion of G0/G1phase cells. Also, overexpression of HOTAIR promotes the migration and invasion ability of lung cancer cells, confirmed by the wound-healing and transwell assays, which are suppressed by overexpression of miR-149-5p. Furthermore, the dual-luciferase reporter assay indicates that miR-149-5p could bind both HOTAIR and the 3′UTR of HNRNPA1. In summary, we find that HOTAIR can regulate HNRNPA1 expression through a ceRNA mechanism by sequester miR-149-5p, which post-transcriptionally targets HNRNPA1, thus promoting lung cancer progression.